Ca2+ ion responsive pickering emulsions stabilized by PSSMA nanoaggregates - Zhao, Chunhua (Langmuir : the ACS journal of surfaces and colloids, 2013)
A novel Ca(2+) ion responsive particulate emulsifier, which is based on copolymer nanoaggregates, is reported in this work. Results from dynamic light scattering (DLS) and cryo-transmission electron microscopy (cryo-TEM) indicate that the formation of poly (4-styrenesulfonic acid-co-maleic acid) sodium salt (PSSMA) nanoaggregates is strongly dependent on Ca(2+) concentration. The PSSMA copolymer only aggregates above a critical Ca(2+) concentration (0.2 M) with an average diameter of 10-40 nm. After dilution with water, PSSMA nanoaggregates are rapidly redissolved again. On the basis of the properties of PSSMA nanoaggregates, Ca(2+) ion responsive Pickering emulsions were successfully prepared. At high Ca(2+) concentrations, the emulsions with high stability against coalescence can be prepared with the size in the submicrometer range as determined by DLS. Cryo-TEM and dynamic interfacial tension results confirm the adsorption of PSSMA nanoaggregates at the interface, which is the key to the stability of the emulsions. More importantly, rapid demulsification can be achieved by dilution with water on demand. It is because, upon dilution with water, PSSMA nanoaggregates undergo a transition from stable nanoaggregates to individual polymer chains, which leads to interfacial desorption of nanoaggregates and rapid demulsification of emulsions. Thus, this finding presents a new manipulation on emulsion stability and is expected to provide a useful guidance in the fields of oil recovery, food science, environment protection, and so on